AB0407 HUMAN PAPILLOMA VIRUS (HPV) INFECTION AND CERVICAL CANCER PREVALENCE IN A PORTUGUESE UNIVERSITY HOSPITAL SINGLE-CENTER SYSTEMIC LUPUS ERYTHEMATOSUS COHORT. (2nd June 2020) - Sousa Morais, J.; Oliveira, D. G.; Faria, R.; Almeida, A.; Brandão, M.; Marinho, A.; Almeida, I.; Farinha, F.; Vasconcelos, C.
Abstract : Background: About 12% of women worldwide are infected with Human Papillomavirus (HPV), the most frequent cause of cervical cancer (CC) - very prevalent (~ 7, 5%) and preventable. National screening efforts are in use in several countries, including Portugal. Patients with Systemic Lupus Erythematosus (SLE) are at increased risk of HPV infection and CC when compared to the healthy population. Objectives: To evaluate the prevalence of HPV infection and rate of incidence of cervical neoplastic lesions in a SLE patient cohort followed at a university hospital. Methods: Retrospective single-center (35 year long, 463 SLE patient cohort) review of all female SLE patients' local and online national health care records on HPV vaccination and CC screening. Results: Of the 463 SLE patients, 420 were women (91%), of which 322 had records on of HPV infection or CC developed. Mean patients' current age was 48 years and all had screening for cervical pathology in the last 3 years. Thirty-three patients (11%) had HPV infection diagnosed at a mean age of 44 years. Twenty-seven (8%) of SLE patients were vaccinated for HPV: 8 (22%) of the infected patients had the vaccine, half after the HPV infection. Despite HPV infection, 49 patients (15%) had developed some cervical lesion, of which 41 (84% of cervical lesion) were suggestive of malignancy, and ultimately CC was diagnosed in 20 women (41%; 6% of total women), with a mean age at diagnosis of 45 years. All CC patients had history of HPV infection, but only 3 women (15%; 0, 9% of total women) had been vaccinated against HPV, 2 after the diagnoses of CC and 1 before. Conclusion: In our population the prevalence of HPV was higher than reported for the general population using the World Health Organization database, conforming the higher risk of HPV infection in SLE patients. The prevalence of cervical cancer, however, was similar to the healthy population. References: [1]https://www.who.int/immunization/diseases/hpv/en/ [2 ]Forman David (2012); "Global Burden of Human Papillomavirus and Related Diseases", Vaccine, Elsevier Volume 30, Supplement 5, 20 November 2012 [3 ]Grein Ingrid (2016), Department of Pediatric Immunology and Rheumatology, Netherland (2016), HPV infection and vaccination in Systemic Lupus Erythematosus patients: what we really should know, Pediatric Rheumatology, 2016 Disclosure of Interests: None declared